Taking care of a patient with type 2 diabetes as part of visiting nurse’s work - Grzegorczyk, Adrianna; Radomska, Aleksandra; Kupcewicz, Ewa (Journal of Education, Health and Sport, 2019)
Introduction. Type II diabetes is a disease whose range of influence is very large. Currently, over 3 million people suffer from diabetes in Poland, of which approximately 2,1 million suffer from type II diabetes. Type II diabetes is a commonly occurring disease and the somewhat responsible lifestyle of the patient is responsible for its development. Her treatment is based not only on pharmacotherapy, which allows to maintain the state of normoglycemia, but also on non-pharmacological methods that enable healthy life. Due to range of influence and the possibility of care in the patient’s environment, the family nurse plays an important role. Her professionalism and preparation of the patient for self-care, can affect the beneficial effect of treatment and adapt the patient to live with the disease at home. Aim of the study. The aim of the study is to duscuss the care problems of a patient with type II diabetes in a home environment, including the care of a family nurse.Case description. The work was based on the individual case method. The data collected about the patient come from own observations, conversations with the patient, analysis of medical records, measurements, and interview with the patient and his family.Discussion. Patients diagnosed with type 2 diabetes often feel confused, they do not know where to go for help. It happens that they do not follow the recommendations, especially those regarding the diet. In addition, patients rarely attempt to change behaviors aimed at preventing complications of diabetes. It is also influenced by their fitness level and age. The role of the nurse at this moment is large. Thanks to the observations and methods used, the nurse allows the patient to meet the deficits in self-care.Conclusions. The effort undertaken by the family nurse brought benefits but did not cause immediate results. Although in most cases the patient was willing to change, he required frequent reminding, instruction and control of the activities undertaken.